Analisis dan Perancangan Sistem Informasi Manajemen Pusat Laktasi : Lactashare - Lia Ninda Safitri; Satrio Agung Wicaksono; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Lactashare is a startup in social movement.The startup aims to disseminate breastmilk donation in Indonesia because of the national exclusive breastmilk target 80% that has not been reached. It affected by several factors, such as working mother, no baby initial milking, low production of breastmilk, and the limited of lactation counselor. Therefore, Lactashare needs a management information system that support the business process. The concept needed to build system base in development of information system is Software Development Life Cycle (SDLC). One of SDLC framework is Use case Driven Object Modeling with UML or named as ICONIX. ICONIX consists of six process. This research provide an insight to build a system that support Lactashare in requrements analysis and system designing phase in ICONIX process. Evaluation is an important activity in Requirements management. Evaluations that used in this research are tracebilty matrix and Correctness. Tracebility matrix refers to the ability to describe and trace the Requirements growth from the start to the end. Correctness used to observe the correct level of a features that made to the described Requirements. The result of this research are artifact of every ICONIX process and traceability matrix and correctness show that design system is correct to the requirement.